RESEARCH ON DYNAMIC SYSTEM RELIABILITY MODEL OF HIGH DIMENSIONAL COPULA FUNCTION - FENG Jun; LIU Wei; TAN Long; LI Yi (Jixie qiangdu)
Aiming at the dynamic mechanical system with multiple failure correlation, the copula function is used to describe the correlation of failure modes among units, and a reliability model of dynamic mechanical system with multiple failure correlations is proposed. The reliability problem of complex system is transformed into multiple two-dimensional pair copula functions by using R-Vine copula function. The optimal R-Vine structure is selected by using MST algorithm. The time-varying parameters in the model are described by nonparametric kernel density estimation（KDE）. The common series parallel system（hybrid system） in mechanical system is modeled and analyzed. Finally, the effectiveness of the model is verified by an example of spacecraft open and close shafting.